2009
DOI: 10.1002/pssb.200880503
|View full text |Cite
|
Sign up to set email alerts
|

G‐mode behaviour of closed ended single wall carbon nanotubes under pressure

Abstract: We have performed high pressure Raman experiments on closed‐ended single wall carbon nanotubes using two different excitation wavelengths: 632.8 nm and 514 nm. We found that the shape of the G‐mode spectrum changes while changing the excitation wavelength at lower pressures, while it becomes similar at 3.5 GPa. In addition we record that the value of the transition pressure, associated with the structural transitions in the tubes, has also changed with changing the excitation wavelength even though we are exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Lebedkin et al report G-band shifts for hydrostatic radial compression with positive slopes of 8.0 ± 0.2, 6.5 ± 0.6, and 8.0 ± 0.5 cm –1 /GPa for small-diameter semiconducting nanotubes dispersed in an aqueous sodium cholate solution at excitation wavelengths of 514, 633, and 785 nm, respectively. G-band shifts for hydrostatic compression have also been reported for dispersed ≈1.4 nm diameter SWCNTs in DOC of 10 ± 0.2 and 7.0 ± 0.2 cm –1 /GPa for empty and water-filled SWCNTs, respectively, and for SWCNT powders of ≈1.4 nm diameter in varying pressure-transmitting media of approximately 6–10 cm –1 /GPa. The similarity of these results across diameter ranges and pressure-transmitting media imply an apparent expansive pressure on the order of 0.2 GPa from alkane-filling. This value allows for an estimation of the strain through the Young’s modulus ( Y ).…”
Section: Results and Discussionmentioning
confidence: 75%
“…Lebedkin et al report G-band shifts for hydrostatic radial compression with positive slopes of 8.0 ± 0.2, 6.5 ± 0.6, and 8.0 ± 0.5 cm –1 /GPa for small-diameter semiconducting nanotubes dispersed in an aqueous sodium cholate solution at excitation wavelengths of 514, 633, and 785 nm, respectively. G-band shifts for hydrostatic compression have also been reported for dispersed ≈1.4 nm diameter SWCNTs in DOC of 10 ± 0.2 and 7.0 ± 0.2 cm –1 /GPa for empty and water-filled SWCNTs, respectively, and for SWCNT powders of ≈1.4 nm diameter in varying pressure-transmitting media of approximately 6–10 cm –1 /GPa. The similarity of these results across diameter ranges and pressure-transmitting media imply an apparent expansive pressure on the order of 0.2 GPa from alkane-filling. This value allows for an estimation of the strain through the Young’s modulus ( Y ).…”
Section: Results and Discussionmentioning
confidence: 75%
“…Experimental difficulties in identifying the collapse transition include the use of samples having wide distributions of diameter, of samples having both open and closed carbon nanotubes which allows partial filling with the pressure transmitting medium [14], of samples consisting of bundles of nanotubes [15], and difficulties due to the evolution of the Raman resonances with pressure [16,17]. Recent experiments on individualized empty (closed) SWCNT [14] showed excellent agreement with improved simulations [5] at an averaged diameter, but were not used for a quantitative experimental determination of the diameter dependence of the collapse pressure.…”
Section: Introductionmentioning
confidence: 99%
“…For small tube diameters with a stable circular cross-section at ambient conditions, it has been shown that a high external pressure causes collapse. This was first shown for SWCNT, where the collapse pressure has been demonstrated to be a function of CNT diameter [41,42,43,44,45,16,46,47,48,49,50,51,52,53,54]. Pressure-induced collapse is also observed for doublewall [55,56,57,58], triple-wall [59] and multi-wall carbon nanotubes [60].…”
Section: Introductionmentioning
confidence: 83%